Trauma and Body Temperature Management in Tropical Regions - Frédéric Lapostolle; Dabor Resiere; Bruno Megarbane; Jean-Marc Pujo (The ASEAN Journal of Military and Preventive Medicine, 2025)
Background: Trauma patients remain vulnerable to hypothermia even in tropical climates. Hypothermia worsens trauma outcomes through deleterious effects on hemostasis and cardiovascular function. Methods: This manuscript summarizes published evidence on trauma-related hypothermia, including mechanisms of heat loss, risk factors, physiologic consequences, and prevention strategies applicable to prehospital trauma care in tropical regions. Results: Hypothermia in trauma is multifactorial and may be triggered by environmental exposure, wet or undressed patients, head trauma, intubation, severe injury, impaired shivering, and infusion of unwarmed fluids. Body temperature below 36°C should be considered clinically relevant. Evidence indicates that hypothermia is associated with increased mortality, coagulopathy, platelet dysfunction, cardiovascular compromise, and greater transfusion requirements. Prevention requires systematic temperature measurement, limiting heat loss, early thermal protection, heated transport environments, warmed intravenous fluids, and rapid transport to hospital care. Conclusion: Trauma-related hypothermia is a poor prognostic factor and should be prevented and corrected worldwide, including in tropical areas. The therapeutic objective is to maintain body temperature at least 36°C.